Understanding injuries during the European Athletics Championships: An epidemiological injury surveilance study - Edouard, P.; Alonso, J.-M.; Depiesse, F.; Branco, P. (New Studies in Athletics, 2014)
Injury data collection represents the first step in injury prevention. The aim of this study was to understand the incidence and characteristics of injuries suffered during the five European Athletics Championships (outdoors and indoors) staged from 2009 to 2013. All newly occurring injuries were reported by national medical teams and/or local organising committee physicians on a standardised injury report form. On average, 79% of all the national medical teams (54% of all countries) participated in the project, covering an average of 86% of the registered athletes. The authors summarise and analyse the data collected and then discuss the practical implications of their work. They conclude that 1) future research should be focused on better understanding the relationships between muscle physiology and biomechanics of performance, the risk factors and mechanisms of both the main injuries observed (hamstring strains, lower leg strains, ankle sprains), and the overuse injuries (prevalence, characteristics, risk factors...) and 2) injury prevention measures should be focused on the preparation of muscles for all movements and constraints (eccentric training), prevention measures against hamstring strains, and the prevention of overuse injuries.